ANOMALOUSLY LOW SODIUM MORB MAGMAS: EVIDENCE FOR DEPLETED MORB OR ANALYTICAL ARTIFACT? - Nielsen R.L.; Christie D.M.; Sprtel F.M. (My University, 1995)
One common characteristic of quenched natural basaltic glass is the presence of microcrystalline halos surrounding many microphenocrysts (spherulites). From our investigations of the composition of basaltic glasses in both quenched lavas and in plagioclase-hosted melt inclusions, we have discovered that quench halo portions of spherulites are over 100 times as susceptible to Na loss during microprobe analysis than normal basaltic glass. This implies that there may be a significant negative bias in published MORB glass Na contents. This, in turn, would result in potential systematic errors in existing models of MORB petrogenesis that are dependent on those data.